Analisis Wacana Kritis Pada Media Massa Daring (Online) Bantennews.co.id Kolom Hukum Edisi Februari 2021 - Asep Yana Yusyama; Ratna Khoirunnisa (Jurnal Ilmiah Dikdaya, 2021)
News in the mass media column has changed the paradigm of society since long time ago. As the times progress, the mass media are also increasingly progressive and dynamic in reporting. Currently, there are many news media in the form of online which is indeed a relatively fast reporting process compared to conventional mass media, especially when examined from a critical discourse point of view. The research question is "What is the description of the Fairclough model's analysis of representation, relation, and identity to the Critical Discourse Analysis (AWK) of the online mass media online mass media bantennews.co.id edition, February 2021. The purpose of this research is to describe the analysis of representations, relations, and the identity of the Fairclough model of Critical Discourse Analysis (AWK) in the online daily law column of bantennews.co.id, February edition, 2021. The method used in this study is a qualitative method, the data collection technique used is documentation technique; As for the data analysis technique used was content review. The data source of this research is Critical Discourse Analysis (AWK) in the online mass media law column bantennews.co.id February edition, 2021. Based on the results of the research, the news text of the bantennews.co.id daily law column contains a discourse on a condition of social phenomena that occurs in Our society is getting more and more various cases of crimes that occur. The motives are different, some have been carried out by suspects from recidivists, unemployed, to the State Civil Service (ASN). Victims who are oppressed in the text of discourse are ordinary people, women, to people who psychologically feel unacceptable in the midst of society.